Analisis Daya Saing Ekspor Wortel - Emmya; A'tri; Euneke; Lucky; Tio; yunita (Universitas Veteran Bangun Nusantara, 2023)
Efforts to reinforce the export capacity of carrots derived from Indonesia has complex problems since the top (on Farm) to downstream. The carrot request at the market of China, Malaysia, Singapore, is still high and this becomes a probabiltas market reduced carrot farmer in the territory of Indonesia. This study intends to examine the competitiveness of carrots derived from Indonesia. Methods of analysis using Revealed Compararative Advantage (RCA) to review the competitiveness of carrots in the Chinese market, Malaysia, Singapore. The results of the analysis show the power of carrots, from Indonesia has competitiveness to many low and high countries